2015
DOI: 10.1371/journal.pone.0140292
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Phenotypic Differences between Mice Producing a Werner Syndrome Helicase Mutant Protein and Wrn Null Mice

Abstract: Werner syndrome (WS) is a premature aging disorder caused by mutations in a RecQ-family DNA helicase, WRN. Mice lacking part of the helicase domain of the WRN orthologue exhibit many phenotypic features of WS, including metabolic abnormalities and a shorter mean life span. In contrast, mice lacking the entire Wrn protein (i.e. Wrn null mice) do not exhibit a premature aging phenotype. In this study, we used a targeted mass spectrometry-based metabolomic approach to identify serum metabolites that are different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Increases in DNA damage and defective DNA repair have been shown to inhibit autophagy 66, 67 . Somatic mtDNA mutation inhibits autophagy, thereby allowing mutated mtDNA to escape degradation and promote mitochondrial dysfunction.…”
Section: Molecular Mechanisms Of Aging In the Heartmentioning
confidence: 99%
“…Increases in DNA damage and defective DNA repair have been shown to inhibit autophagy 66, 67 . Somatic mtDNA mutation inhibits autophagy, thereby allowing mutated mtDNA to escape degradation and promote mitochondrial dysfunction.…”
Section: Molecular Mechanisms Of Aging In the Heartmentioning
confidence: 99%
“…We have reported that the mutant Wrn protein (Wrn Dhel ) is mislocalized in the cytoplasm of Wrn Δhel/Δhel mice (11). Further microscopy analyses indicated a colocalization of Wrn Dhel proteins with the PDI.…”
Section: Ratios Of Specific Metabolites Indicate Various Pathway Anommentioning
confidence: 91%
“…Oxidative stress in the liver tissue of Wrn Dhel/Dhel /Gulo 2/2 mice We had found that the liver of Wrn Δhel/Δhel and Gulo 2/2 mice treated with low amounts of ascorbate (,0.01% in drinking water) exhibit an oxidative stress in the ER (11,21,29). The liver plays a pivotal role in nutrient, hormone, lipid, and metabolic waste product processing, thereby maintaining body homeostasis (30).…”
Section: Ratios Of Specific Metabolites Indicate Various Pathway Anommentioning
confidence: 99%
See 2 more Smart Citations